DARI KEPEMIMPINAN HINGGA BUDAYA PELAYANAN: MEMBANGUN MODEL PELAYANAN ISLAMI DI SEKOLAH ISLAM TERPADU DAN PESANTREN - Jumadi Subur; Irmayanti; Eva Zamzamiyatul Musyarofah (PT Wahana Global Education, 2025)
This research aims to formulate a comprehensive and holistic Islamic service model for implementation in Integrated Islamic Schools and Islamic Boarding Schools (Pesantren), as a solution to the challenges of service practices that tend to be transactional and lacking a spiritual dimension. The proposed model coherently synthesizes Greenleaf and Spears' theoretical framework of servant leadership with Fry's spiritual leadership and fundamental Islamic principles. This approach uniquely integrates the observed external dimensions of service behavior with the internal spiritual motivational foundation that drives it. Using a qualitative research methodology with a process of theme identification, categorical coding, and conceptual synthesis, this research produces a dualistic model. The philosophical core of this model is